A wave energy harvesting system based on the double-wing flywheel for unmanned surface vessels. (1st October 2022) - Dai, Chutian; Zhou, Xianzheng; Zhang, Zutao; Wu, Xiaoping; Li, Hai; Xu, Ping; Jin, Zhou; Li, Dongyang
Graphical abstract: In this paper, a wave energy harvesting system based on the double-wing flywheel is proposed for extending the work life of unmanned surface vessels (USVs). The system can be divided into four modules: wave energy capture module, motion conversion module, electromagnetic transducer module, and circuit module. The device is installed inside the USV. The wave energy capture module captures the energy of USV vibration. The vibrating mass block drives the nut in the motion conversion module to vibrate up and down and then drives the screw to rotate. Through the one-way bearing on the screw, the bidirectional rotational motion of the screw is converted into the relative one-way rotation of the electromagnetic transducer module. The electromagnetic transducer module mainly consists of a magnet flywheel and coil flywheel, both of which are driven by the motion conversion to one-way rotate relatively. The relatively-one-way rotation of the electromagnetic transducer module improves the power generation efficiency of the device. The generated electrical energy will be passed through the circuit module to store in the supercapacitor and eventually power the sensor. A prototype was fabricated, and the power generation performance of the system was evaluated by bench test under different sinusoidal excitations. Analyzing the experimental results, it was found that the average power output is 40.24 W, given 1.0 Hz-80 mm sinusoidal vibration input. The comparative experiments show that the device with the double-wing flywheel mechanism increases the maximum average power by 51.64% compared to the non-MMR device. The USV sensors and the operating time analysis show that the system can support sensors to operate intermittently, which shows the potential of the wave energy harvesting device for use on USV. Highlights: A double-wing flywheel-based wave energy harvesting system is proposed for USV. An efficient double-wing flywheel electromagnetic transducer is proposed. Dynamics model of double-wing flywheel electromagnetic transducer. The output power is increased by 51.64% by the double-wing flywheel mechanism. Abstract: Unmanned surface vessels (USVs) are increasingly used in environmental protection, safe search, rescue, and maritime investigations. These USVs are generally battery or diesel-powered for sailing, and the limited size of USVs results in a lower working life of USVs. This paper proposes a wave energy harvesting system for USVs based on a double-wing flywheel. This system is installed in the hull of the USV and converts the wave energy that causes the USV to vibrate into electrical power. The system can be divided into four modules: wave energy capture module, motion conversion module, electromagnetic transducer module, and circuit module. The wave energy capture module captures the mechanical energy of USV vibration caused by waves and the change of driving state and converts it into the mechanical energy of the mass block vibration. The motion conversion module uses a screw-nut mechanism and the double-wing flywheel mechanism to convert the reciprocating vibrations of the mass block into the relative one-way rotation of the magnet flywheel and the coil flywheel. The electromagnetic transducer module converts the mechanical energy of flywheels into electrical energy and transmits it to the circuit module. The circuit module rectifies the current and stores the electrical energy in a supercapacitor, eventually used to power various sensors. Simulations and experiments were conducted on the proposed wave energy harvesting system. MTS bench experiments confirm a 51.64% increase in energy harvesting power than an energy harvesting device without a mechanical motion rectifier (MMR). Data transfer experiments show that the system can capture wave energy to drive temperature and humidity sensors for data transmission. The results show that the energy harvesting system can be practically applied to USVs to improve their service life.